Making citrus fruits healthy - Das, A K (Indian Horticulture, 2019)
The Phytophthora spp. causes foot rot, root rot, crown rot, gummosis, leaf fall and brown rot diseases on citrus inflicting severe losses. Water regulation, clean stock, sanitation, host resistance, bioagents and chemicals are among the controls that can be implemented. Effective disease control is rarely achieved through the application of a single disease-control method. In order to limit the risks associated with outbreaks of Phytophthora diseases on citrus, a number of different approaches should be taken in an integrated manner.